Utilização de sistemas estruturais metálicos no atual cenário da construção civil brasileira: estudo de caso para a montagem de estrutura e cobertura de galpão industrial de médio porte - Almeida, Wanderley Ribeiro (2017)
The use and diffusion of metallic structural systems have been shown to be extremely important in the current Brazilian economic situation. The use of this constructive system within a market highly demanding by new technologies and constructive methods, finds in the civil construction the ideal place to be diffused. The purpose of this work is to characterize the use of this constructive system, since it is a fact that, in the case of industrial constructions, the use of metallic structures is largely due to the use of these elements, whether they are combined with one another or alone with others Constructive systems. The methodology used to achieve this goal was visits to manufacturing companies, construction projects, literary research, manuals, books, monographs and a case study related to this work. Through these materials, it was possible to present and detail several subjects within the context approached, among them the importance of the use of metallic structural systems. The sum of all this information leads to a comparison between the existing structural systems in the market and to emphasize the importance and advantages of building steel.